Penggunaan Akun Tiktok @husainbasyasman Sebagai Media Dakwah Terhadap Minat Mahasiswa Komunikasi Penyiaran Islam IAI-ALAZIS Dalam Pembuatan Konten Dakwah - Fathia Nur Shabrina; Muhammad N Abdurrazaq; Alfi Satria (CV. ITTC INDONESIA, 2023)
One of the communication technologies that can be used as an intermediary to convey da'wah messages is social media, one of which is Tiktok. The younger generation in this case is expected to participate in spreading the teachings of Islam through the creation of da'wah content with creative and innovative ideas. This study uses a qualitative field research method with descriptive analysis. Interviews, observation, and documentation were used to collect data. According to the findings of this study Husain Basyasman used Tiktok as a propaganda medium where he shared his knowledge, about aqidah, morals and sharia knowledge. The way he delivered da'wah was also easy to understand and creative. The impact is the increase in their religious knowledge. In addition, students also have a desire to create da'wah content so that a better society can be realized. On the other hand, there are also students who are not interested in making da'wah content because they feel that their religious knowledge is not quite enough.